Influence of Customer Generosity to Intention in Participating to Future Charity Directly or Mediated by Positive Emotion - Dwidienawati, Diena; Arief, Mts; Bramantoro Abdinagoro, Sri (International Journal of Engineering and Technology, 2018)
This study taps into the questions of whether there is a direct relationship between customer generosity to customer intention in participating in charity program or there is a mediating role of positive emotion in the relationship. Previous study showed inconsistency on the motivation of people being generous. We hypothesize that there are direct and indirect relationship between customer generosity to customer intention in participating in future charity program. Using descriptive quantitative method, this study was conducted in Indonesian adults in several cities in Indonesia. A structured questionnaire regarding the construct of the study was designed using 6 Likert scale. Data from total 100 returned questionnaires was analyzed with PLS-SEM. The result of the study confirms the hypotheses that people has intention to participate in future charity program is not only motivated by the positive emotion but also motivated pure empathy.Â Â Â Â